Windshield for vehicle and its manufacturing method

A laminated glass windshield with a low-porosity light-shielding layer over the power feeding section addresses residual stress from lead-free soldering, enhancing breaking strength and visibility, achieved through a specific manufacturing process.

JP2025001519APending Publication Date: 2025-01-08AGC INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023101147
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2025-01-08

AI Technical Summary

Technical Problem

The use of lead-free solder in bonding conductors to vehicle windshields generates residual stress due to thermal expansion differences, leading to cracks and reduced breaking strength of the glass plate.

Method used

A vehicle windshield design with a laminated glass structure where the power feeding section is formed on a light-shielding layer with a porosity of 12% or less, using lead-free solder to bond the conductor and terminal, and a manufacturing method that includes forming a ceramic paste layer and a silver-containing paste layer followed by firing to create the light-shielding and conductor layers.

Benefits of technology

The design increases the breaking strength of the glass plate before and after terminal attachment by minimizing porosity in the light-shielding layer, ensuring the power feeding section is not visible and maintaining structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001519000001_ABST
    Figure 2025001519000001_ABST
Patent Text Reader

Abstract

To provide a windshield for vehicle and its manufacturing method, in which: the windshield for vehicle includes a part in which a conductor is joined with a terminal by using lead-free solder; the windshield for vehicle can be designed so that a glass plate thereof to which the terminal has been attached has an improved breaking strength.SOLUTION: A windshield (1) for vehicle includes a laminated glass (10) in which a first glass plate (11) and a second glass plate (13) are bonded together with an intermediate film (12) interposed therebetween, in which the laminated glass includes a glass plate with a terminal (13X) including the second glass plate, a conductor (20) including a terminal joint portion where terminals are joined, and the terminal (102) being joined to the terminal joint portion of the conductor through lead-free solder (101); the conductor (20) includes a feeding portion for feeding electricity to an electric function portion; the feeding portion includes the terminal joint portion; the glass plate with the terminal includes a light-shielding layer (BL2) between the second glass plate and at least a part of the conductor including the feeding portion; and a porosity of at least a forming region of the feeding portion in the light-shielding layer is 12% or lower.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to vehicle windshields and methods of manufacturing the same. [Background technology]

[0002] For window glass of a vehicle such as an automobile, a laminated glass in which a plurality of glass plates are bonded together or a tempered glass is preferably used. In general, a glass plate as a material for a vehicle windshield has a light-shielding layer formed in a peripheral region and is processed into a shape having a curved surface by thermoforming. There is known a vehicle windshield that includes an electrical function part or includes a conductor connected to the electrical function part and a power supply member such as a harness and a cable. The electrical function part may include a heating wire, a heating layer, an antenna, a light control layer, a light emitting element, and a combination thereof. In this specification, a glass sheet having an electric conductor is referred to as a "glass sheet with an electric conductor".

[0003] The light-shielding layer can be formed, for example, by coating and firing a ceramic paste containing a black pigment and glass frit. The conductor can be formed, for example, by coating and firing a silver-containing paste containing silver powder and glass frit. The firing of the ceramic paste and the silver-containing paste can be carried out simultaneously with the thermoforming of the glass plate.

[0004] An optical device including an optical device such as an ADAS (Advanced Driver Assistance systems) camera, LiDAR (Light Detection And Ranging), radar, and optical sensor that acquires information in front of the vehicle for autonomous driving and to prevent collision accidents, and a housing called a bracket or the like that houses the optical device may be installed on the inner surface of the windshield. In such a configuration, in order to improve the sensing accuracy of the optical device, a heating wire may be formed on the glass part in front of the optical device to prevent fogging and frost.

[0005] The conductor-attached glass plate on which the above-mentioned optical device is mounted can have, in a plan view, an optical device mounting area in which the optical device is mounted, a light-transmitting portion located within this optical device mounting area through which incident light from the outside to the optical device and / or emitted light from the optical device passes, and a light-shielding layer surrounding at least a portion of this light-transmitting portion. The conductor for the optical device can include a heating wire formed inside the light-transmitting portion, a power supply portion formed outside the light-transmitting portion and including a pair of power supply electrodes (also called bus bars), and a connection wire formed outside the light-transmitting portion for connecting the heating wire and the power supply portion. A power supply member such as a harness and a cable is joined to each power supply electrode. In the above-mentioned conductor for optical devices, the heating wire formed in the light-transmitting portion is designed to be thin so as to be difficult to be seen by people outside the vehicle and so as not to affect the acquisition of information about the area ahead of the vehicle by the optical device through the light-transmitting portion. On the other hand, the power supply portion is designed to be thicker than the heating wire because it is not intended to generate heat and requires an area for joining the power supply member. Therefore, the power supply portion is generally formed on a light-shielding layer so as not to be seen by people outside the vehicle. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2021-18932 [Patent Document 2] International Publication No. 2022 / 176814 Summary of the Invention [Problem to be solved by the invention]

[0007] Conventionally, the power supply portion and the power supply member are joined by using solder. For example, a terminal is fixed to the tip of a power supply member such as a wire harness, and this terminal is joined to a power supply part included in a conductor using solder. There are lead solder and lead-free solder. In recent years, there has been concern about the impact of lead on the environment, and legal restrictions on lead solder are becoming more widespread, so the use of lead-free solder is desired. Patent Documents 1 and 2 disclose vehicle window glass in which a light-shielding layer is formed on a laminated glass, a conductor including a plurality of power supply parts is formed on the light-shielding layer, and a terminal is joined to each power supply part via lead-free solder (claims 1, 24, 25, 30, Figs. 1, 5, and 6, etc. of Patent Document 1; claims 1, 11, 15, and Fig. 2, etc. of Patent Document 2).

[0008] Generally, the melting point of lead-free solder is higher than that of lead-containing solder, for example, about 220°C, and soldering must be performed at a higher temperature (for example, about 300°C). When a conductor and a terminal are joined in a glass plate with a conductor by using lead-free solder, the glass plate is locally heated to a high temperature and cooled from a high temperature to room temperature. During the cooling, a difference in the amount of thermal contraction occurs between the glass plate and the lead-free solder due to the difference between the thermal expansion coefficient of the glass plate and the thermal expansion coefficient of the lead-free solder, and distortion occurs between the glass plate and the lead-free solder, causing stress (specifically, tensile stress) in the glass plate with a conductor. This stress may remain even after the temperature is lowered. This residual stress may cause cracks in the glass plate after the window glass is manufactured. In addition, since lead-free solder does not contain lead, which has a low elasticity, it has a higher elasticity than lead-containing solder and is less likely to deform. Therefore, the residual stress generated in the glass plate with a conductor is less likely to be alleviated. For these reasons, when the conductor and the terminal are joined with lead-free solder, residual stress may occur in the glass plate after joining, which may result in cracks occurring after manufacturing. In this specification, a glass plate having an electric conductor and a terminal is referred to as a "glass plate with terminals."

[0009] If the breaking strength of the glass sheet after terminal attachment is low, there is a risk of glass cracking when an external force is applied to the glass sheet. In particular, when a terminal is joined to a power supply part formed on a light-shielding layer using lead-free solder, the breaking strength of the glass sheet after terminal attachment tends to decrease. It is preferable to increase the breaking strength of the glass sheet after terminal attachment in soldering using lead-free solder while designing the conductor so that it is difficult for people outside the vehicle to see. In this specification, the "breaking strength of a glass plate before or after terminal attachment" refers to the load at which glass breaks when a load is applied to the glass before or after terminal attachment, and can be measured by the method described later in the "Examples" section.

[0010] The present disclosure has been made in consideration of the above circumstances, and aims to provide a vehicle windshield and a manufacturing method thereof that includes a portion where a conductor and a terminal are joined using lead-free solder, can be designed so that the power supply part of the conductor is not visible to people outside the vehicle, and can increase the breaking strength of the glass sheet after the terminals are attached. [Means for solving the problem]

[0011] The present disclosure provides the following vehicle windshields and methods for manufacturing the same [1] to

[12] . [1] A laminated glass in which a first glass sheet and a second glass sheet are bonded together via an interlayer film, The laminated glass is a vehicle windshield comprising: the second glass sheet; a glass sheet with terminals, the glass sheet having a conductor formed on a surface of the second glass sheet opposite to the interlayer film side and having a terminal joint portion to which a terminal is joined, and a terminal joined onto the terminal joint portion of the conductor via lead-free solder; the electrical conductor includes an electrical function or is electrically connected to an electrical function; the conductor includes a power supply portion for supplying power to the electrical function portion, the power supply portion including the terminal joint portion; the terminal-equipped glass plate has a light-shielding layer between the second glass plate and at least a portion of the conductor including the power supply portion, The light-shielding layer has a porosity of 12% or less at least in a region where the power supply portion is formed.

[0012] [2] The vehicle windshield according to [1], wherein the light-shielding layer has a porosity of 8% or less at least in the region where the power supply portion is formed. [3] The vehicle windshield according to [2], wherein the light-shielding layer has a porosity of 3% or less at least in the area where the power supply portion is formed. [4] The vehicle windshield according to any one of [1] to [3], wherein the light-shielding layer contains a black pigment and a glass frit. [5] The vehicle windshield according to any one of [1] to [4], wherein the conductor contains silver and glass frit.

[0013] [6] The glass plate with terminals has, in a plan view, an optical device mounting area in which an optical device is mounted, and a light-transmitting portion located within the optical device mounting area and through which incident light from the outside to the optical device and / or emitted light from the optical device passes, the light-shielding layer is formed so as to surround at least a portion of the light-transmitting portion in a plan view, The vehicle windshield according to any one of [1] to [5], wherein the conductor includes a heating wire formed inside the translucent portion, the power supply portion formed outside the translucent portion, and connection wiring formed outside the translucent portion and connecting the heating wire and the power supply portion.

[0014] [7] The vehicle windshield according to [6], wherein in the glass plate with terminals, the connection wiring and the power supply portion are formed on the light-shielding layer. [8] The vehicle windshield according to any one of [1] to [7], wherein a power supply member made of a round wire or foil-shaped conductor is fixed to the terminal.

[0015] [9] A step (X) of preparing a glass plate with a conductor in which the light-shielding layer and the conductor are formed on the surface of the second glass plate; a step (Y) of bonding the first glass plate and the conductor-attached glass plate together via the interlayer film; and (Z) a step of joining the terminal to the terminal joint portion of the conductor via lead-free solder, Process (X) is A step (S11) of applying a ceramic paste containing a black pigment and a glass frit as materials for the light-shielding layer onto the surface of the second glass plate to form a ceramic paste layer; A step (S12) of applying a silver-containing paste containing silver and glass frit as the conductive material onto the surface of the second glass plate to form a silver-containing paste layer; and (S13) firing the ceramic paste layer and the silver-containing paste layer to form the light-shielding layer and the conductor.

[0016]

[10] A step (X) of preparing a glass plate with a conductor, in which the light-shielding layer and the conductor are formed on the surface of the second glass plate; a step (Y) of bonding the first glass plate and the conductor-attached glass plate together via the interlayer film; and (Z) a step of joining the terminal to the terminal joint portion of the conductor via lead-free solder, Process (X) is A step (S21) of applying a ceramic paste containing a black pigment and a glass frit onto the surface of the second glass plate and firing the paste to form the light-shielding layer; and (S22) applying a silver-containing paste containing silver and glass frit onto the surface of the second glass plate, and firing the paste to form the conductor.

[0017]

[11] The method for manufacturing a vehicle windshield according to [9] or

[10] , wherein the total content of organic components in the ceramic paste is 30 mass% or less.

[12] The method for producing a vehicle windshield according to any one of [9] to

[11] , wherein a total content of polymer components in the ceramic paste is 5 mass % or less. Effect of the Invention

[0018] In the vehicle windshield of the present disclosure, at least the power supply portion of the conductor included in the terminal-attached glass plate is formed on the light-shielding layer, so that the power supply portion of the conductor can be designed not to be visible to people outside the vehicle. By limiting the porosity of at least the power supply portion-forming region of the light-shielding layer, the breaking strength of the glass plate before and after the terminals are attached can be increased. [Brief description of the drawings]

[0019] [Figure 1A] 1 is an overall plan view of a vehicle windshield according to an embodiment of the present invention; [Figure 1B] FIG. 2 is an overall plan view of a first glass plate. [Diagram 2] FIG. 1B is a partially enlarged plan view of FIG. 1A. [Diagram 3] FIG. 3 is a cross-sectional view taken along line III-III in FIG. [Figure 4] FIG. 4 is a cross-sectional view taken along line IV-IV in FIG. [Diagram 5] 3 is a cross-sectional view taken along line VV in FIG. 2. [Figure 6] FIG. 6 is a partially enlarged cross-sectional view of FIG. [Figure 7A] 3A to 3C are process diagrams of a method for manufacturing the vehicle windshield of the embodiment. [Figure 7B] 3A to 3C are process diagrams of a method for manufacturing the vehicle windshield of the embodiment. [Figure 7C] 3A to 3C are process diagrams of a method for manufacturing the vehicle windshield of the embodiment. [Figure 8] 2 is an image showing a measurement example of the porosity of the glass laminate obtained in Example 1. [Figure 9] 4 is an image showing a measurement example of the porosity of the glass laminate obtained in Example 2. [Figure 10] 1 is an image showing a measurement example of the porosity of the glass laminate obtained in Example 3. [Figure 11] 1 is a graph showing the evaluation results of the glass laminates obtained in Examples 1 to 3. [Figure 12]1 is a graph showing the evaluation results of the glass laminates obtained in Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Generally, thin film structures are referred to as "films" and "sheets" depending on their thickness. In this specification, there is no clear distinction between them. Therefore, in this specification, "films" may include "sheets". In this specification, the term "approximately" attached to a shape means a shape that has been partially changed, such as a chamfered shape with rounded corners, a shape with part of the shape missing, or a shape with an arbitrary small shape added to the shape. In this specification, unless otherwise specified, "glass sheet" refers to untempered glass. In this specification, unless otherwise specified, the term "surface of a glass plate" refers to a main surface having a large area, excluding the end faces (also called side faces) of a glass plate. In this specification, unless otherwise specified, "up and down," "left and right," "vertical and horizontal," and "inside and outside" refer to "up and down," "left and right," "vertical and horizontal," and "inside and outside" when the vehicle windshield is fitted into the vehicle (actual usage state) and viewed from the inside of the vehicle.

[0021] In this specification, "lead-free solder" refers to solder that is substantially free of lead, and the lead content in lead-free solder is 500 ppm or less. In this specification, unless otherwise specified, when lead-free solder is described as being "substantially free of a certain metal element other than lead," it means that the content of that metal element is 1000 ppm or less. In this specification, unless otherwise specified, normal temperature is 20 to 25°C. In this specification, unless otherwise specified, "polymer" refers to a component having a molecular weight of 100 or greater. In this specification, unless otherwise specified, the "molecular weight of a polymer" refers to the weight average molecular weight (Mw) or number average molecular weight (Mn) calculated as standard polystyrene by gel permeation chromatography (GPC). In this specification, unless otherwise specified, the use of "to" indicating a numerical range means that the numerical values ​​before and after it are included as the lower limit and upper limit. Hereinafter, an embodiment of the present invention will be described.

[0022] [Vehicle windshield] The present disclosure relates to a vehicle windshield including a laminated glass in which a first glass plate and a second glass plate are bonded together via an interlayer film. The first glass sheet may be an exterior glass sheet, and the second glass sheet may be an interior glass sheet. The type of glass plate that is the material of the laminated glass is not particularly limited, and examples thereof include soda lime glass, borosilicate glass, aluminosilicate glass, lithium silicate glass, quartz glass, sapphire glass, and non-alkali glass.

[0023] The thickness of the laminated glass is not particularly limited, and is preferably 2 to 6 mm for use as a vehicle windshield. The thickness of the glass plate on the inside of the vehicle and the thickness of the glass plate on the outside of the vehicle may be the same or different. The thickness of the glass plate on the inside of the vehicle is preferably 0.3 to 2.3 mm. If the thickness of the glass plate on the inside of the vehicle is 0.3 mm or more, the handling property is good, and if it is 2.3 mm or less, the mass is not too large. The thickness of the glass plate on the outside of the vehicle is preferably 1.0 to 3.0 mm. If the thickness of the glass plate on the outside of the vehicle is 1.0 mm or more, the strength of the performance of resistance to flying stones and the like is sufficient, and if it is 3.0 mm or less, the mass of the laminated glass is not too large, which is preferable in terms of fuel efficiency of the vehicle. If the thickness of the glass plate on the outside of the vehicle and the thickness of the glass plate on the inside of the vehicle are both 1.8 mm or less, the laminated glass can be made both lightweight and soundproof, which is preferable.

[0024] The vehicle windshield may have a curved shape such that the vehicle exterior side is convex when installed in the vehicle. When the vehicle windshield is a laminated glass, the glass sheet on the vehicle interior side and the glass sheet on the vehicle exterior side may both have a curved shape such that the vehicle exterior side is convex. The vehicle windshield may have a single curved shape curved only in one direction, either the left-right direction or the up-down direction, or a compound curved shape curved in both the left-right direction and the up-down direction. The radius of curvature of the vehicle windshield may be 2000 to 11000 mm. The radius of curvature of the vehicle windshield in the left-right direction and the up-down direction may be the same or different. Gravity forming, press forming, roller forming, etc. are used for bending the vehicle windshield.

[0025] The laminated glass may have a coating having functions such as water repellency, low reflectivity, low radiation, ultraviolet ray shielding, infrared ray shielding, and coloring, on at least a partial region of the surface. The laminated glass may have, in at least a partial region inside, a film having functions such as low reflectivity, low emissivity, ultraviolet shielding, infrared shielding, coloring, etc. At least a partial region of the interlayer film of the laminated glass may have functions such as ultraviolet shielding, infrared shielding, coloring, etc. The interlayer of the laminated glass may be a single layer or a laminated layer.

[0026] In the vehicle windshield of the present disclosure, the laminated glass includes a second glass sheet, and a terminal-attached glass sheet having a conductor formed on a surface of the second glass sheet opposite to the interlayer film side and having a terminal joint to which a terminal is joined, and a terminal joined onto the terminal joint of the conductor via lead-free solder. In this specification, the "terminal joint" of a conductor refers to the portion of the conductor directly below the lead-free solder.

[0027] In the glass plate with terminals, the conductor includes an electrical function part or is electrically connected to an electrical function part. The electrical functional portion may include one or more heating wires, heating layers, antennas, dimming layers, light-emitting elements, and combinations thereof. Light-emitting elements may include LEDs (Light Emitting Diodes) and OLEDs (Organic Light Emitting Diodes). The one or more electric heating wires or layers can remove and prevent fog, frost, snow, ice, etc. The one or more electric heating wires or layers can be used, for example, to prevent windshield wipers from freezing; to improve the sensing accuracy of optical devices, including optical instruments such as cameras and radars; etc. The electrical functional portion can be manufactured by a known method.

[0028] In the glass plate with terminals, the conductor includes a power supply portion for supplying power to the electrical functional portion. The power supply portion may include a pair of power supply electrodes (also referred to as a pair of bus bars), and each of the power supply electrodes may include a terminal joint portion. For example, one of the power supply electrodes is a positive electrode and is connected to a power source or a signal source provided in the vehicle via a power supply member, and the other power supply electrode is a negative electrode and is connected to the vehicle body (earth) via a power supply member. Note that the number of power supply electrodes for the positive electrode may be one or more, and the number of power supply electrodes for the negative electrode may be one or more. When the conductor is connected to the electrical function unit, the conductor and the electrical function unit may be formed on the same glass surface or on different glass surfaces. The conductor having the terminal joint can be formed by applying a silver-containing paste containing silver powder and glass frit onto a glass plate and firing the paste. The glass frit in the silver-containing paste can be a known one, and the metal element can be one containing Na, Al, Si, P, Zn, Ba, Bi, etc.

[0029] A power supply member made of a round or foil conductor can be fixed to the terminal. In this specification, the term "conductor" includes a covered conductor in which one or more conductors are covered with an insulating material. A covered conductor is preferable as the power supply member. Specific examples of the power supply member include a harness and a cable. Examples of the round conductor include a wire harness. Examples of the foil conductor include a flat harness and a flexible printed circuit board. The power supply member has an exposed conductor portion, and the terminal is fixed to the exposed conductor portion. The material of the exposed conductor portion is not particularly limited, and examples thereof include Cu, Al, Ag, Au, Ti, Sn, Zn, alloys thereof, and combinations thereof. The exposed conductor portion may be a main metal whose surface is plated with another metal. The exposed conductor portion may have a thin oxide film on its surface.

[0030] Lead-free solder is solder that contains little or no lead, and known solders can be used. Examples of lead-free solder include SnAg-based solders that contain Sn and Ag; SnAgCu (SAC)-based solders that contain Sn, Ag, and Cu; SnZnBi-based solders that contain Sn, Zn, and Bi; SnCu-based solders that contain Sn and Cu; SnZnAl-based solders that contain Sn, Zn, and Al; and In-based solders that contain In.

[0031] From the viewpoint of environmental resistance, etc., preferred lead-free solders include, for example, SnAg-based lead-free solders that contain Sn and Ag and are substantially free of Sb, Cu and In; and SnAgCu (SAC)-based lead-free solders that contain Sn, Ag and Cu and are substantially free of Sb and In. The melting point of lead-free solder such as SnAg-based and SnAgCu-based solder is higher than that of leaded solder, for example, about 220° C. When lead-free solder such as SnAg-based and SnAgCu-based solder is used, the solder bonding temperature is, for example, about 300° C. The present disclosure is particularly effective when lead-free solder such as SnAg-based and SnAgCu-based solder with a high melting point is used.

[0032] Preferred embodiments of the SnAg-based and SnAgCu-based lead-free solders will be described below. The Sn content in the SnAg-based and SnAgCu-based lead-free solders is not particularly limited, and is preferably 95% by mass or more, more preferably 95 to 98.5% by mass, and particularly preferably 96 to 98% by mass. If the Sn content is 95% by mass or more (the Ag content is 5% by mass or less), the melting point of the lead-free solder can be relatively low, so that the soldering temperature can be relatively low and the temperature rise of the glass plate can be relatively small. As a result, the residual stress generated in the glass plate and the resulting cracking of the glass plate can be suppressed.

[0033] Generally, when using Sn-based lead-free solder that does not contain Ag, the Sn in the lead-free solder and the Ag in the conductor are highly compatible, so the Ag in the terminal joint of the conductor is likely to penetrate into the lead-free solder containing Sn, which is known as "silver erosion." In this case, the terminal joint may discolor due to deterioration and thinning, resulting in poor appearance. When lead-free solder containing Sn and Ag is used, the Sn in the lead-free solder has already formed a compound with Ag, which prevents the Ag in the terminal joint of the conductor from penetrating into the lead-free solder, thereby preventing discoloration of the terminal joint and the resulting poor appearance. The Ag content in the lead-free solder is preferably 1.5 to 5 mass%, more preferably 2 to 4 mass%. If the Ag content is 1.5 mass% or more, the penetration of Ag in the terminal joint of the conductor into the lead-free solder can be effectively suppressed, and good joint strength can be obtained. If the Ag content is 5 mass% or less, the material cost of the lead-free solder can be kept low, and the melting point of the lead-free solder can be kept relatively low.

[0034] The lead-free solder may contain Cu as a metal element other than Sn and Ag. The amount of Cu contained in the lead-free solder is not particularly limited, and is preferably 1 mass % or less, and more preferably 0.5 mass % or less. An example of the composition of SnAg-based lead-free solder is Sn: 98% by mass, Ag: 2% by mass, etc. An example of the composition of SnAgCu-based lead-free solder is Sn: 96.5% by mass, Ag: 3.0% by mass, Cu: 0.5% by mass, etc.

[0035] From the viewpoint of reducing thermal stress on the glass plate when terminals are attached, an In-based lead-free solder containing In, which is a low melting point solder, is also preferable. As for In-based lead-free solder, SnIn-based lead-free solder containing Sn and In and substantially free of Sb, Ag and Cu; SnAgIn based lead-free solder containing Sn, Ag and In, and substantially free of Sb, Cu, Bi, Ni and Zn; SnAgInCu based lead-free solder containing Sn, Ag, In and Cu, and substantially free of Sb, Bi, Ni and Zn; SnAgInBi based lead-free solder containing Sn, Ag, In and Bi, and substantially free of Sb, Cu, Ni and Zn; Examples of such lead-free solder include SnAgInNiCuZn-based lead-free solders that contain Sn, Ag, In, Ni, Cu and Zn and are substantially free of Sb and Bi.

[0036] The electrical conductor power supply portion included in the terminal-equipped glass plate is designed to be thicker than the heating wire and the connection wiring, so it is preferable to design it so that it is not visible to people outside the vehicle. The glass plate with terminals on which the optical device is mounted has, in a plan view, an optical device mounting area in which the optical device is mounted, and a light-transmitting portion located within this optical device mounting area through which incident light from the outside to the optical device and / or emitted light from the optical device passes. In this glass plate with terminals, the light-shielding layer is formed so as to surround at least a portion of the light-transmitting portion in a planar view, and the conductor can include a heating wire formed inside the light-transmitting portion, a power supply portion formed outside the light-transmitting portion, and connection wiring formed outside the light-transmitting portion and connecting the heating wire and the power supply portion. In the above-mentioned conductor for optical devices, the heating wire formed within the translucent portion is designed to be thin so as to be difficult to see by people outside the vehicle and so as not to affect the acquisition by the optical device of information about the area in front of the vehicle through the translucent portion. In the present disclosure, in the conductor for the optical device, at least the power supply portion is designed to be formed on a light-shielding layer so that the power supply portion of the conductor is not visible to people outside the vehicle. It is preferable that the connection wiring and the power supply portion are formed on the light-shielding layer.

[0037] The light-shielding layer can be formed by a known method, for example, by applying a ceramic paste containing a black pigment and glass frit to a predetermined area on the surface of a glass plate and firing it. The thickness of the light-shielding layer is not particularly limited, and is, for example, 5 to 20 μm. As the glass frit in the ceramic paste, a known one can be used, and as the metal element, one containing Na, Al, Si, P, Zn, Ba, Bi, etc. can be used.

[0038] The ceramic paste may contain one or more organic solvents, such as α-terpineol, butyl carbitol, butyl carbitol acetate, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, ethylene glycol mono-2-ethylhexyl ether, diethylene glycol mono-2-ethylhexyl ether, ethylene glycol monohexyl ether, diethylene glycol monohexyl ether, ethylene glycol monobutyl ether acetate, and diethylene glycol monobutyl ether. The ceramic paste may include one or more polymeric components, such as, for example, ethyl cellulose, acrylic resins, styrene resins, phenolic resins, and butyral resins.

[0039] According to the research of the inventors, it has been found that during the process of firing the ceramic paste layer, organic components in the ceramic paste layer (specifically, organic solvents and polymer components, etc.) may decompose and volatilize, resulting in the formation of voids in the light-shielding layer. Conventionally, when forming a conductor on a light-shielding layer, a method is generally used in which a ceramic paste is applied to a glass plate, dried to form a ceramic paste layer, a silver-containing paste is applied thereon, dried to form a silver-containing paste layer, and these layers are simultaneously fired. In this method, since the ceramic paste layer is fired while covered with the silver-containing paste layer, it is considered that the organic components or decomposition products thereof in the light-shielding layer are difficult to remove, and voids may be formed.

[0040] Generally, when a terminal is joined to a power supply portion formed on a light-shielding layer using lead-free solder, the breaking strength of the glass plate after the terminal is attached tends to decrease. According to the research of the present inventors, it has been found that the higher the porosity of the light-shielding layer, the lower the breaking strength of the glass plate before and after terminal attachment. The reason for this is not necessarily clear, but is presumed to be as follows. The presence of voids in the light-shielding layer can cause the light-shielding layer to have a lower density or a lower uniformity. The presence of voids in the light-shielding layer can also be the starting point of cracks. For these reasons, it is believed that the presence of voids in the light-shielding layer reduces the strength of the light-shielding layer.

[0041] According to the research of the present inventors, it has been found that the lower the porosity of the light-shielding layer, the higher the breaking strength of the glass plate before and after terminal attachment. In the vehicle windshield of the present disclosure, the breaking strength of the glass plate before and after terminal attachment can be increased by limiting the porosity of at least the power supply part formation region of the light-shielding layer. The porosity of at least the power supply part formation region of the light-shielding layer is preferably 12% or less, more preferably 10% or less, even more preferably 8% or less, even more preferably 5% or less, particularly preferably 3% or less, and most preferably 2% or less. The porosity of the light-shielding layer can be measured by the method described in the section [Examples] below.

[0042] Methods for effectively reducing the porosity of the light-shielding layer include limiting the total content of organic components in the ceramic paste; limiting the total content of polymeric components in the ceramic paste; limiting the molecular weight of the organic components in the ceramic paste; firing the ceramic paste layer before applying the silver-containing paste; and combinations of these. The total content of organic components in the ceramic paste is preferably 30% by mass or less, more preferably 25% by mass or less, and particularly preferably 20% by mass or less. There is no particular lower limit, and it is, for example, 15% by mass. The total content of the polymer components in the ceramic paste is usually 0.5 to 15% by mass. The upper limit is preferably 10% by mass, more preferably 5% by mass. The lower limit is not particularly limited, and is, for example, 2% by mass.

[0043] [One embodiment] The present disclosure is preferably applicable to a vehicle windshield to which an optical device is attached. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS A structure of a vehicle windshield according to an embodiment of the present invention will be described with reference to the drawings. FIG. 1A is an overall plan view of a vehicle windshield of this embodiment. FIG. 1B is an overall plan view of a first glass plate. FIG. 2 is a partially enlarged plan view of FIG. 1A. FIGS. 1A and 2 are views before terminal joining. In FIGS. 1A, 1B, and 2, the front side of the figures is the vehicle interior side, and the back side is the vehicle exterior side. FIG. 3 is a cross-sectional view taken along line III-III in FIG. 2. FIG. 4 is a cross-sectional view taken along line IV-IV in FIG. 2. FIG. 5 is a cross-sectional view taken along line VV in FIG. 2. In FIGS. 3 to 5, the upper side of the figures is the vehicle exterior side, and the lower side of the figures is the vehicle interior side. All of these figures are schematic views, and in order to make them easier to see, the scale of each component in each figure is appropriately changed from the actual one.

[0044] The planar shape of the vehicle windshield 1 can be designed as appropriate, and may be, for example, a generally curved shape of a plate having a generally trapezoidal shape in plan view as shown in FIG. 1A. As shown in FIG. 5, a vehicle windshield 1 of this embodiment includes a laminated glass 10 in which a first glass plate 11 and a second glass plate 13 are bonded together with an interlayer film 12 interposed therebetween. In this embodiment, the laminated glass 10 includes a second glass plate 13, a terminal-equipped glass plate 13X formed on a surface S4 (the surface facing the vehicle interior) of the second glass plate 13 opposite the intermediate film 12 side and having a terminal joint 20T to which a terminal 102 is joined, and a terminal 102 joined onto the terminal joint 20T of the conductor 20 via lead-free solder 101. In the illustrated example, the laminated glass 10 is formed by bonding a first glass plate 11 and a terminal-equipped glass plate 13X together with an interlayer film 12 interposed therebetween. In this embodiment, the first glass plate 11 is a glass plate on the outer side of the vehicle, and the terminal-equipped glass plate 13X is a glass plate on the inner side of the vehicle.

[0045] As shown in FIG. 1A, the vehicle windshield 1 has an optical device mounting area OP in which an optical device is mounted, and a light-transmitting portion TP located within the optical device mounting area OP and through which incident light from the outside to the optical device and / or emitted light from the optical device passes. As shown in the figure, the light-transmitting portion TP can be formed in a region relatively close to one end side 10E of the vehicle windshield 1 (the upper end side in the illustrated example).

[0046] The optical device may include, for example, optical instruments such as ADAS (Advanced Driver Assistance systems) cameras, LiDAR (Light Detection And Ranging), radar, and optical sensors that acquire information in front of the vehicle for the purposes of autonomous driving and preventing collision accidents, and a housing called a bracket or the like that houses these instruments. The shapes of the optical device mounting area OP and the light-transmitting part TP can be appropriately designed according to the shape of the optical device, and examples of such shapes include a substantially trapezoidal shape and a substantially rectangular shape. The shapes of the optical device mounting area OP and the light-transmitting part TP may be similar or non-similar. In the illustrated example, the shapes of the optical device mounting area OP and the light-transmitting part TP are substantially trapezoidal.

[0047] As shown in FIG. 1A and FIG. 5, a second light-shielding layer BL2 is formed in a predetermined region on a surface S4 (the surface facing the vehicle interior) of the second glass plate 13 opposite the interlayer 12 side. As shown in FIG. 1A, the formation area of ​​the second light-shielding layer BL2 can include the area excluding the light-transmitting portion TP from the optical device mounting area OP, the area surrounding the optical device mounting area OP, and the peripheral area of ​​the vehicle windshield 1.

[0048] In the illustrated example, the formation area of ​​the second light-shielding layer BL2 includes the area excluding the light-transmitting portion TP from the optical device mounting area OP and the area surrounding the optical device mounting area OP, as well as an area R21 excluding the light-transmitting portion TP from a substantially trapezoidal area defined by one end edge 10E (the upper end edge in the illustrated example) of the laminated glass 10 and edges B21 to B23, and a peripheral area R22 of the vehicle windshield 1. In the illustrated example, the second light-shielding layer BL2 surrounds all four sides of the light-transmitting portion TP, but it is sufficient that the second light-shielding layer BL2 surrounds at least a portion of the light-transmitting portion TP, and may, for example, surround only three sides of the light-transmitting portion TP which has an approximately trapezoidal or approximately rectangular shape. The wavelength range of light transmitted through the light-transmitting portion TP is not particularly limited, and may be, for example, the visible light range, the infrared light range, or a range from the visible light range to the infrared light range.

[0049] As shown in Figures 1B and 5, a first light-shielding layer BL1 can be formed, if necessary, in a specified area of ​​the surface S2 of the first glass plate 11 on the interlayer 12 side (the surface facing the vehicle interior, the surface facing the second glass plate 13). As shown in Figure 1B, the formation area of ​​the first light-shielding layer BL1, like the second light-shielding layer BL2, can include the area excluding the light-transmitting portion TP from the optical device mounting area OP, the area surrounding the optical device mounting area OP, and the peripheral area of ​​the vehicle windshield 1. In the illustrated example, the formation area of ​​the first light-shielding layer BL1, like the second light-shielding layer BL2, includes the area excluding the light-transmitting portion TP from the optical device mounting area OP and the area surrounding the optical device mounting area OP, and also includes an area R11 excluding the light-transmitting portion TP from a substantially trapezoidal area defined by one end edge 10E (the upper end edge in the illustrated example) of the laminated glass 10 and edges B11 to B13, and a peripheral area R12 of the vehicle windshield 1.

[0050] The planar shape of the region R11 of the first light-shielding layer BL1 and the planar shape of the region R21 of the second light-shielding layer BL2 can be designed independently, and the planar shapes of these regions may be the same or different. For example, the planar shape of the region R11 of the first light-shielding layer BL1 may be designed to be wider than the region R21 of the second light-shielding layer BL2. Similarly, the planar shape of the region R12 of the first light-shielding layer BL1 and the planar shape of the region R22 of the second light-shielding layer BL2 can be designed independently of each other, and the planar shapes of these regions may be the same or different.

[0051] 2, in this embodiment, the conductor 20 includes an electrical function unit made of a heating wire 20L formed inside the light-transmitting portion TP. The conductor 20 further includes a power supply unit made of a pair of power supply electrodes (a pair of bus bars) 20B formed outside the light-transmitting portion TP. The conductor 20 further includes two connection wires 20M formed outside the light-transmitting portion TP and connecting the heating wire 20L and the pair of power supply electrodes (a pair of bus bars) 20B.

[0052] By providing a heating wire 20L for preventing fogging and frost in an area including a light-transmitting portion TP located in front of optical equipment such as a camera and radar included in the optical device, the sensing accuracy of the optical device can be improved. The number of heating wires 20L, the number of connecting wires 20M, the number of power supply electrodes 20B, the line pattern and arrangement pattern of the heating wires 20L and connecting wires 20M, the shape and arrangement pattern of the power supply electrodes 20B, etc. can be designed as appropriate. For example, when viewed from above, if the heating wire 20L is folded back so as to cross the light-transmitting portion TP a plurality of times or more, frost and water droplets adhering to the light-transmitting portion TP can be efficiently removed, which is preferable. The line width of the heating wire 20L and / or the connection wire 20M from one power supply electrode to the other power supply electrode may be substantially the same or may vary.

[0053] As shown in FIG. 5, in this embodiment, the conductor 20 is formed on a surface S4 (the surface facing the vehicle interior) opposite the interlayer 12 side of the terminal-fitted glass plate 13X. The terminal-equipped glass plate 13X has a second light-shielding layer BL2 between the second glass plate 13 and the power supply portion (a pair of power supply electrodes 20B) of the conductor 20. In other words, in the conductor 20, at least the power supply portion (a pair of power supply electrodes 20B) is formed on the second light-shielding layer BL2. Preferably, the connection wiring 20M and the power supply portion (a pair of power supply electrodes 20B) are formed on the second light-shielding layer BL2.

[0054] In the vehicle windshield 1 of the present embodiment, the porosity of at least the power supply portion forming region of the second light-shielding layer BL2 is limited, thereby making it possible to increase the breaking strength of the second glass sheet 13 and the laminated glass 10 before terminals are attached, and of the second glass sheet 13 and the laminated glass 10 after terminals are attached. The porosity of at least the power supply portion forming region of the second light-shielding layer BL2 is preferably 12% or less, more preferably 10% or less, even more preferably 8% or less, still more preferably 5% or less, particularly preferably 3% or less, and most preferably 2% or less.

[0055] Each of the pair of power supply electrodes (pair of bus bars) 20B includes a terminal joint portion 20T, and a terminal 102 is joined onto the terminal joint portion 20T of the conductor 20 via lead-free solder 101. A power supply member 103 made of a round wire or foil-shaped conductor is fixed to the terminal 102. The terminal joint 20T of the conductor 20 is the portion directly below the lead-free solder 101. In the drawing, the area of ​​the terminal joint 20T is the area sandwiched between two dashed lines T1 and T2. Note that the position of the terminal joint 20T of the conductor 20 is not clearly determined from the beginning. In the power supply electrode 20B, the portion directly below the lead-free solder 101 after the terminal 102 is joined via the lead-free solder 101 is the terminal joint 20T.

[0056] Fig. 6 is a partially enlarged cross-sectional view of the cross section of the laminated structure of the terminal 102 / lead-free solder 101 / power supply electrode 20B / second light-shielding layer BL2 / second glass plate 13 shown in Fig. 5, as viewed from the left side of Fig. 5. Here, the laminated structure is upside down for ease of visualization. The power supply member 103 is preferably a round or foil-shaped conductor, more preferably a round or foil-shaped coated conductor, and more preferably a wire harness, flat harness, or the like. The tip of the power supply member 103 is an exposed conductor portion, and the terminal 102 is fixed to this exposed conductor portion. A known crimp terminal is preferable as the terminal 102. The crimp terminal preferably has a power supply member joint 102A (see FIG. 5) that contacts the tip end (exposed conductor portion) of the power supply member 103, and a solder joint 102B (see FIGS. 5 and 6) that contacts the lead-free solder 101.

[0057] When a wire harness is used as the power supply member 103, a preferred crimp terminal is one that includes a power supply member joint 102A having a cylindrical shape or the like that is crimped to fix the tip end (exposed conductor portion) of the wire harness, and a bridge-shaped portion having solder joints 102B at both ends, as shown in Figures 5 and 6. The crimp terminal may have one solder joint 102B without a bridge-shaped portion.

[0058] The terminal 102 is preferably a metal terminal. The metal constituting the terminal is not particularly limited, and examples thereof include metals such as copper, iron, chromium, and zinc; alloys containing one or more metal elements such as copper, iron, chromium, and zinc; and combinations thereof. Examples of alloys include brass. The surface of the terminal 102 may be subjected to a surface treatment such as tin plating. At least a portion of the terminal 102 may be covered with an insulating material. The thickness of the terminal 102 is not particularly limited, and is preferably 0.4 to 0.8 mm. The terminal 102 made of a single material can be manufactured, for example, by punching a metal plate (press processing using a punching die) to obtain a metal plate of a desired size, and bending the metal plate. For example, a terminal 102 (preferably a crimp terminal) is fixed by crimping to a tip portion (exposed conductor portion) of the power supply member 103, and the terminal 102 is joined to a terminal joint portion 20T in the power supply electrode 20B via lead-free solder 101. The tip portion (exposed conductor portion) of the power supply member 103 and the terminal 102 may be connected by soldering or by welding.

[0059] As shown in FIGS. 1A, 1B, 2 and 3, in this embodiment, the first light-shielding layer BL1 and the second light-shielding layer BL2 are not formed in the light-transmitting portion TP. In the conductor 20, the heating wire 20L is designed to be thin so as to be difficult to see by people outside the vehicle and so as not to affect the acquisition of information about the area ahead of the vehicle by an optical device via the light-transmitting portion TP. The power supply portion (the pair of power supply electrodes 20B) is formed on the second light-shielding layer BL2, and is therefore not visible to people outside the vehicle. The connection wiring 20M is preferably formed on the second light-shielding layer BL2, and can be designed so as not to be visible to people outside the vehicle.

[0060] The housing of the optical device can be attached to the glass plate with terminals 13X using one or more materials including an adhesive, preferably a combination of an adhesive and a double-sided tape. Examples of adhesives include epoxy adhesives, urethane adhesives, silicone adhesives, modified silicone adhesives, melamine adhesives, phenolic adhesives, acrylic adhesives, and combinations thereof. The adhesives may be one-component or two-component. Unless otherwise specified, the adhesives are one-component. Specific examples of adhesives include modified silicone adhesives, epoxy adhesives, two-component urethane adhesives, thermosetting urethane adhesives, and second-generation acrylic adhesives (SGA). Among them, urethane adhesives are preferred from the viewpoints of the stability and flexibility of adhesion to the housing of the optical device. In this embodiment, as shown in FIG. 2, in a terminal-fitted glass plate 13X, the outer periphery of an optical device mounting region OP can be designed so as to surround a light-transmitting portion TP and a conductor 20 for the optical device in a plan view.

[0061] [Manufacturing method] The method for manufacturing a vehicle windshield according to the present disclosure includes: A step (X) of preparing a glass plate with a conductor, the glass plate having a light-shielding layer and a conductor formed on a surface of a second glass plate; a step (Y) of bonding the first glass plate and the conductor-attached glass plate via an interlayer film; and a step (Z) of joining a terminal to the terminal joining portion of the conductor via lead-free solder.

[0062] Process (X) is A step (S11) of applying a ceramic paste containing a black pigment and a glass frit, which are materials for a light-shielding layer, onto a surface of a second glass plate to form a ceramic paste layer; A step (S12) of applying a silver-containing paste containing silver and glass frit as a conductive material onto the surface of the second glass plate to form a silver-containing paste layer; The method may sequentially include a step (S13) of firing the ceramic paste layer and the silver-containing paste layer to form a light-shielding layer and a conductor.

[0063] Hereinafter, an example of a method for manufacturing the vehicle windshield of the above embodiment will be described with reference to the drawings. 7A to 7C are schematic cross-sectional views corresponding to FIG. (Process (X)) <Process (S11)> First, a ceramic paste containing a black pigment and glass frit as a material for a light-shielding layer is applied to a predetermined area on the surface S4 of the second glass plate 13, and then dried to form a ceramic paste layer. If necessary, a ceramic paste layer may be formed in a similar manner on a predetermined area on the surface S2 of the first glass plate 11. The drying conditions can be appropriately designed depending on the paste composition, and for example, 120 to 150°C and approximately 5 minutes are preferable.

[0064] <Process (S12)> Next, a silver-containing paste containing silver powder and glass frit is applied to a predetermined area on the surface S4 of the second glass plate 13 on which the ceramic paste layer has been formed, and then dried to form a silver-containing paste layer. The drying conditions can be appropriately designed depending on the paste composition, and for example, 120 to 150°C and about 5 minutes are preferable.

[0065] <Process (S13)> Next, the second glass sheet 13 is heated to a temperature equal to or higher than its softening point and bent. In this process, the ceramic paste layer and the silver-containing paste layer are simultaneously fired to form the second light-shielding layer BL2 and the conductor 20. The first glass sheet 11 is bent in the same manner. The ceramic paste layer formed on the first glass sheet 11 as required is fired in this process to become the first light-shielding layer BL1. After firing, each glass sheet is slowly cooled. After these steps, as shown in FIG. 7A, a first glass plate 11 having a first light-shielding layer BL1 as necessary, and a conductor-attached glass plate 13Y having a second light-shielding layer BL2 and a conductor 20 on one surface S4 of the second glass plate 13 are obtained.

[0066] The ceramic paste layer and the silver-containing paste layer do not have to be fired at the same time. After the ceramic paste is applied onto the surface S4 of the second glass plate 13, dried and fired to form the second light-shielding layer BL2, the silver-containing paste may be applied thereon, dried and fired to form the conductor 20. In this case, step (X) is A step (S21) of applying a ceramic paste containing a black pigment and a glass frit onto a surface of a second glass plate and firing the paste to form a light-shielding layer; and (S22) applying a silver-containing paste containing silver and glass frit onto the surface of the second glass sheet, followed by firing the paste to form a conductor including a terminal joint portion. In this method, the ceramic paste layer is fired before the silver-containing paste is applied, so that the organic components in the ceramic paste layer are easily removed, and the porosity in the second light-shielding layer BL2 can be effectively reduced.

[0067] (Process (Y)) Next, as shown in FIG. 7A, a first glass plate 11 having a first light-shielding layer BL1 as required and a glass plate 13Y with a conductor are bonded together via a resin film 12F made of the material of the intermediate film 12, using a known method. The resin constituting the resin film 12F is not particularly limited, and is preferably one or more resins selected from the group consisting of polyvinyl butyral (PVB), ethylene vinyl acetate copolymer (EVA), cycloolefin polymer (COP), polyurethane (PU), and ionomer resin. The resin film 12F may contain one or more additives other than resins as necessary. Examples of additives include colorants such as pigments. The resin film 12F may be colorless and transparent or colored and transparent. The resin film 12F may have a single layer structure or a laminate structure of two or more layers.

[0068] The lamination can be performed by thermocompression bonding. Examples of the thermocompression bonding method include a method in which a provisional laminate obtained by overlapping a plurality of members as shown in Fig. 7A is placed in a rubber bag or the like and heated in a vacuum; a method in which the provisional laminate is pressurized and heated using an automatic pressurized heat treatment device, an autoclave, or the like; and a combination of these. The thermocompression bonding conditions of temperature, pressure and time are not particularly limited and are designed according to the type and temperature of the resin film 12F. The thermocompression bonding conditions may be such that the resin film 12F is softened, sufficiently pressurized, and the first glass plate 11 and the conductor-attached glass plate 13Y are sufficiently bonded via the resin. Thermocompression bonding may be performed in multiple stages by changing the method or conditions. The constituent resin of the resin film 12F softens and spreads so as to fill the space between the first glass plate 11 and the conductor-attached glass plate 13Y. After these steps, the laminated glass 10 shown in FIG. 7B is obtained.

[0069] (Process (Z)) Next, as shown in Fig. 7C, terminals 102 are joined onto terminal joints 20T included in each power supply electrode 20B via lead-free solder 101. Power supply members 103, preferably made of a round or foil-shaped conductor, are fixed (preferably by crimping) to terminals 102 in advance by a known method. For details about solder joints, see also Fig. 6.

[0070] Soldering can be performed by known methods, preferably using a soldering iron or resistance heating. When using a soldering iron, the bonding can be performed, for example, as follows. An appropriate amount (e.g., 0.05 to 0.10 g) of lead-free solder is applied to each solder joint of the terminal. This terminal is then placed on top of the terminal joint of the conductor. In this state, the tip of a soldering iron set to a temperature equal to or higher than the melting point of the lead-free solder is pressed against the solder joint of the terminal to heat and melt the lead-free solder. After that, the soldering iron is removed from the terminal and the lead-free solder is allowed to solidify by natural cooling. It is recommended to apply flux to the surface of the unmelted lead-free solder and / or the surface of the solder joint of the terminal before soldering. The flux melts the metal oxide film, resulting in a good joint. It is recommended to place an appropriate amount of lead-free solder on the tip of the soldering iron and heat it to melt it before soldering. This solder is called pre-solder and can increase the thermal conductivity during soldering.

[0071] Generally, to bond a conductor and solder well, it is necessary to form an alloy layer at the bonding interface between the conductor and the solder, which contains an alloy of one or more metal elements contained in the conductor and multiple metal elements contained in the solder. For this reason, the solder is heated to its melting point or higher to perform solder bonding. The melting point of lead-free solder such as SnAg-based and SnAgCu-based solder is, for example, about 220°C. In this case, the solder bonding temperature is preferably, for example, about 300°C. In the manner described above, the vehicle windshield 1 of the present embodiment is manufactured.

[0072] As described above, according to the present disclosure, it is possible to provide a vehicle windshield that includes a portion where a conductor and a terminal are joined using lead-free solder, can be designed so that the power supply part of the conductor is not visible to people outside the vehicle, and can increase the breaking strength of the glass sheet after the terminals are attached. EXAMPLES

[0073] The present invention will be described below based on examples, but the present invention is not limited to these. Examples 1 and 11 to 13 are examples.

[0074] [Evaluation items and evaluation methods] The evaluation items and evaluation methods are as follows. (porosity) The cross section of the evaluation glass laminate 1 (lamination structure: conductor / light-shielding layer / glass plate, before terminal attachment) was observed. The observation area was the laminate structure part of conductor / light-shielding layer / glass plate. If necessary, it was cut in the thickness direction using a high-speed diamond wheel saw (Precis's "Mecatome T180") and polished using an automatic polishing device (Precis's "Mecatech 234"). Furthermore, if necessary, it was subjected to ion milling treatment using Hitachi High-Tech's "ArBlade 5000". Using a field emission scanning electron microscope (FE-SEM, Hitachi High-Technologies Corporation, "Regulus8220"), images of three randomly selected points on the cut surface were taken at 2500x magnification at a voltage of 3 kV. Multiple voids of various sizes were confirmed in the light-shielding layer. In the cross-sectional SEM images, the voids were visible in black or gray. If necessary, relatively light gray voids were filled in black by image processing. Images were processed using commercially available image analysis software (Mitani Shoji Co., Ltd., "WinRooF2018") to determine the porosity of the light-shielding layer as the ratio of the cross-sectional area of ​​the black region corresponding to the voids to the total cross-sectional area of ​​the light-shielding layer. The average porosity of the three cross-sectional SEM images was calculated, and this was used as the porosity (%) data.

[0075] (Breaking strength) A ring bending test was carried out in a room temperature (20 to 25°C) environment using an autograph (Shimadzu Corporation "AGS-X", maximum load: 5 kN) in accordance with ASTM-C1499-1. The glass laminate 1 for evaluation (lamination structure: conductor / light-shielding layer / glass plate, before terminal attachment) was placed on a support ring with a diameter of 98 mm, with the surface on which the conductor was formed facing down. A load ring with a diameter of 46 mm was placed on this glass laminate for evaluation. The central axis of the support ring, the central axis of the glass plate, and the central axis of the load ring were aligned. A load was applied to the periphery of the conductor of the glass laminate for evaluation by a load ring. The load was continuously increased so that the displacement of the glass plate was 1 mm / min, and the load at which the glass plate broke was defined as the breaking strength. For each condition, a total of 15 to 20 samples were measured, and the maximum, minimum, or average value (also called the average breaking strength) was calculated. Unless otherwise specified, the average value was used as the breaking strength data.

[0076] [Manufacturing method of evaluation glass laminate 1 (lamination structure: conductor / light-shielding layer / glass plate, before terminal attachment)] A 100 mm x 100 mm square unreinforced glass plate (AGC "VFL", green color) with a thickness of 3.5 mm was prepared. A ceramic paste for forming a light-shielding layer containing a black pigment and glass frit was applied to one surface of the glass plate by a screen printing method, and then dried to form a ceramic paste layer. The drying conditions were 120°C and 15 minutes. Next, a silver-containing paste for forming a conductor, which contains silver powder and glass frit, was applied onto the ceramic paste layer by screen printing and then dried at 120° C. for 10 minutes to form a conductive paste layer. Next, the ceramic paste layer and the conductive paste layer were fired. The temperature was raised from room temperature (20 to 25°C) to 600°C or 640°C at a rate of about 2°C / sec, and fired at this temperature (600°C or 640°C) for 400 seconds, and then naturally cooled to room temperature (20 to 25°C). In this way, a light-shielding layer and a conductor were formed.

[0077] The planar shape of the light-shielding layer was a square of 90 mm × 90 mm, and its center and diagonal were aligned with the center and diagonal of the glass plate. The thickness of the light-shielding layer was about 15 μm. The planar shape of the conductor was a square of 30 mm × 30 mm, with its center and diagonal aligned with the center and diagonal of the glass plate. The thickness of the conductor was about 7 μm. In this manner, a glass laminate 1 for evaluation (before terminals were attached) having a laminated structure of conductor / light-shielding layer / glass plate was produced.

[0078] [Examples 1-3] In each of Examples 1 to 3, a common commercially available silver-containing paste (AgP1) was used, and the type (composition) of the ceramic paste and / or the firing temperature conditions were changed to produce and evaluate a glass laminate 1 for evaluation (lamination structure: conductor / light-shielding layer / glass plate, before terminal attachment). In Example 1, a commercially available ceramic paste (BP1) was used as the ceramic paste, and the firing temperature was set to 600°C. In Example 2, a ceramic paste (BP2) was used in which 4 mass% of crosslinked acrylic resin particles (AR1) ("Crosslinked acrylic monodisperse particles MX-1000" manufactured by Soken Chemical Asia Co., Ltd., average particle size: 10 μm) was added to the ceramic paste (BP1), and the firing temperature was set to 600°C. In Example 3, a ceramic paste (BP3) in which 2 mass % of crosslinked acrylic resin particles (AR1) was added to the ceramic paste (BP1) was used as the ceramic paste, and the firing temperature was set to 640°C. The ceramic pastes (BP1) to (BP3) had a total organic component content of 30 mass % or less and a total polymer component content of 5 mass % or less. In these examples, conditions not described in the specification are common conditions.

[0079] [Summary of results for Examples 1 to 3] Examples of porosity measurements are shown in FIGS. The upper image in FIG. 8 is an example of a cross-sectional SEM image of evaluation glass laminate 1 obtained in Example 1 (cross-sectional SEM image (SEM1-1)). The center image in FIG. 8 is a cross-sectional SEM image (SEM1-2) after the gray voids in the above cross-sectional SEM image (SEM1-1) have been painted black by image processing. The lower diagram in FIG. 8 is an image (SEM1-3) showing measurement data of the porosity performed using image analysis software on the above cross-sectional SEM image (SEM1-2).

[0080] The upper image in FIG. 9 is an example of a cross-sectional SEM image of evaluation glass laminate 1 obtained in Example 2 (cross-sectional SEM image (SEM2-1)). The center image in FIG. 9 is a cross-sectional SEM image (SEM2-2) after the gray voids in the above cross-sectional SEM image (SEM2-1) have been painted black by image processing. The lower diagram in FIG. 9 is an image (SEM2-3) showing measurement data of the porosity performed on the above cross-sectional SEM image (SEM2-2) using image analysis software.

[0081] The upper image of FIG. 10 is an example of a cross-sectional SEM image of evaluation glass laminate 1 obtained in Example 3 (cross-sectional SEM image (SEM3-1)). The center image in FIG. 10 is a cross-sectional SEM image (SEM3-2) after the gray voids in the above cross-sectional SEM image (SEM3-1) have been painted black by image processing. The lower diagram in FIG. 10 is an image (SEM3-3) showing measurement data of the porosity performed using image analysis software on the above cross-sectional SEM image (SEM3-2).

[0082] The main production conditions and evaluation results (data on porosity and breaking strength) of the glass laminates obtained in Examples 1 to 3 are shown in Table 1. The evaluation results (data on porosity and breaking strength) of the glass laminates obtained in Examples 1 to 3 are shown in Figs. 11 and 12. 8 to 10, larger pores were observed in Examples 2 and 3 in which resin particles were added to the ceramic paste compared to Example 1. A greater number of pores were observed in Examples 2 and 3 in which resin particles were added to the ceramic paste compared to Example 1. Under the same firing temperature conditions, the porosity of the light-shielding layer tended to be higher when the amount of polymer component in the ceramic paste was greater. Also, when a polymer component was added to the ceramic paste, the porosity of the light-shielding layer tended to be higher when the firing temperature was higher. When ceramic paste (BP2), in which 4 mass% of cross-linked acrylic resin particles (AR1) were added to ceramic paste (BP1), was used and the firing temperature was set to 640°C, so that too many air bubbles were generated that the glass laminate cracked during firing.

[0083] As shown in Table 1, and Figs. 11 and 12, there was a tendency that the breaking strength of the glass laminate decreased as the porosity of the light-shielding layer increased. As shown in FIG. 12, for the glass laminates obtained in Examples 1 to 3, data was plotted with average fracture strength (MPa) as x and porosity (%) as y, and an approximate equation for the plotted data was found to be y = 0.4518x + 25.12.

[0084] [Examples 11-13] In each of Examples 11 to 13, a glass laminate 1 for evaluation (laminate structure: conductor / light-shielding layer / glass plate, before terminal attachment) was produced in the same manner as in Example 1, except that the type (composition) of the ceramic paste was changed, and the breaking strength was measured. In Example 11, a commercially available ceramic paste (BP11) was used as the ceramic paste. In Example 12, a commercially available ceramic paste (BP12) was used as the ceramic paste. In Example 13, a commercially available ceramic paste (BP13) was used as the ceramic paste. The ceramic pastes (BP11) to (BP13) had a total organic component content of 30 mass% or less and a total polymer component content of 5 mass% or less. In these examples, conditions not described in the specification were common conditions. Table 2 shows the main production conditions and the evaluation results of the average breaking strength of the glass laminates obtained in Examples 11 to 13.

[0085] [Reference examples R1~R4] As Reference Example R1, average data on the average breaking strength of the glass laminates obtained in Examples 11 to 13 was determined. The porosity of the light-shielding layer was calculated by applying the data on the breaking strength of Examples 11 to 13 and Reference Example R1 to the above approximate formula (y=0.4518x+25.12). These data are shown in Table 2. For Reference Examples R2 to R4, the porosity of the light-shielding layer was calculated by applying the breaking strength data of 28.0 MPa, 29.0 MPa, or 30.0 MPa to the above approximate formula (y=0.4518x+25.12). These data are shown in Table 3.

[0086] [Table 1]

[0087] [Table 2]

[0088] [Table 3]

[0089] [Summary of the results of Examples 11 to 13 and Reference Examples R1 to R4] The data shown in Table 3 indicates that if the porosity of the light-shielding layer is 12% or less, the breaking strength of the glass laminate before terminal attachment can be made at a sufficiently high level, for example, 28 MPa or more, 29 MPa or more, or 30 MPa or more. The breaking strength of the glass laminates before terminal attachment obtained in Examples 11 to 13 was 30 MPa or more. It is estimated that the porosity of the light-shielding layer of each of the glass laminates before terminal attachment obtained in these examples was 12% or less.

[0090] The present invention is not limited to the above-described embodiment and examples, and the design can be appropriately modified without departing from the spirit of the present invention. [Explanation of symbols]

[0091] 1: vehicle windshield, 10: laminated glass, 11: first glass plate, 12: intermediate film, 13: second glass plate, 13X: glass plate with terminal, 13Y: glass plate with conductor, 20: conductor, 20L: heating wire, 20M: connecting wiring, 20B: power supply electrode, 20T: terminal joint, 101: lead-free solder, 102: terminal, 103: power supply member, BL1: first light-shielding layer, BL2: second light-shielding layer, OP: optical device mounting area, TP: light-transmitting portion.

Claims

1. The laminated glass includes a first glass plate and a second glass plate bonded together via an interlayer film, The laminated glass is a vehicle windshield comprising: the second glass sheet; a glass sheet with terminals, the glass sheet having a conductor formed on a surface of the second glass sheet opposite to the interlayer film side and having a terminal joint portion to which a terminal is joined, and a terminal joined onto the terminal joint portion of the conductor via lead-free solder, the electrical conductor includes an electrical function or is electrically connected to an electrical function; the conductor includes a power supply portion for supplying power to the electrical function portion, the power supply portion including the terminal joint portion; the terminal-equipped glass plate has a light-shielding layer between the second glass plate and at least a portion of the conductor including the power supply portion, The light-shielding layer has a porosity of 12% or less at least in a region where the power supply portion is formed.

2. The vehicle windshield according to claim 1 , wherein the light-shielding layer has a porosity of 8% or less at least in a region where the power supply portion is formed.

3. The vehicle windshield according to claim 2 , wherein the light-shielding layer has a porosity of 3% or less at least in a region where the power supply portion is formed.

4. The vehicle windshield according to claim 1 , wherein the light-shielding layer contains a black pigment and a glass frit.

5. The vehicle windshield according to claim 1 or 2, wherein the conductor comprises silver and glass frit.

6. the glass plate with terminals has, in a plan view, an optical device mounting region in which an optical device is mounted, and a light-transmitting portion located within the optical device mounting region and through which incident light from the outside to the optical device and / or emitted light from the optical device passes; the light-shielding layer is formed so as to surround at least a portion of the light-transmitting portion in a plan view, 3. The vehicle windshield according to claim 1, wherein the conductor includes a heating wire formed inside the translucent portion, the power supply portion formed outside the translucent portion, and a connection wiring formed outside the translucent portion and connecting the heating wire and the power supply portion.

7. The vehicle windshield according to claim 6 , wherein in the glass plate with terminals, the connection wiring and the power supply portion are formed on the light-shielding layer.

8. 3. The vehicle windshield according to claim 1, wherein a power supply member made of a round or foil conductor is fixed to the terminal.

9. a step (X) of preparing a glass plate with a conductor in which the light-shielding layer and the conductor are formed on the surface of the second glass plate; a step (Y) of bonding the first glass plate and the conductor-attached glass plate together via the interlayer film; and a step (Z) of joining the terminal to the terminal joint portion of the conductor via lead-free solder, Step (X) is A step (S11) of applying a ceramic paste containing a black pigment and a glass frit as materials for the light-shielding layer onto the surface of the second glass plate to form a ceramic paste layer; A step (S12) of applying a silver-containing paste containing silver and glass frit as the conductive material onto the surface of the second glass plate to form a silver-containing paste layer; 2. The method for manufacturing a vehicle windshield according to claim 1, further comprising the steps of: firing the ceramic paste layer and the silver-containing paste layer to form the light-shielding layer and the conductor (S13).

10. a step (X) of preparing a glass plate with a conductor in which the light-shielding layer and the conductor are formed on the surface of the second glass plate; a step (Y) of bonding the first glass plate and the conductor-attached glass plate together via the interlayer film; and a step (Z) of joining the terminal to the terminal joint portion of the conductor via lead-free solder, Step (X) is A step (S21) of applying a ceramic paste containing a black pigment and a glass frit onto the surface of the second glass plate and firing the paste to form the light-shielding layer; and (S22) applying a silver-containing paste containing silver and glass frit onto the surface of the second glass plate and firing the paste to form the conductor.

11. The method for manufacturing a vehicle windshield according to claim 9 or 10, wherein a total content of organic components in the ceramic paste is 30 mass % or less.

12. The method for manufacturing a vehicle windshield according to claim 9 or 10, wherein a total content of polymer components in the ceramic paste is 5 mass % or less.

Citation Information

Patent Citations

  • Glass plate module

    JP2021018932A

  • Vehicle glass

    WO2022176814A1